Current Issues of Automobile Insurance - Eva Ducháčková (European Financial and Accounting Journal, 2011)
Auto insurance belongs to the most important areas of the insurance market from the quantitative point of view and based on its significance in covering auto-related risks. The significance of damage impact, particularly in liability insurance, requires a high degree of regulation. Standard products, auto liability and collision insurance are following the overall changes in insurance policies and are adjusting to the changing conditions. One of the major issues in the auto insurance in the Czech Republic and internationally is a toughening competition which results in changing insurance premiums. At the same time, new forms of auto insurance are introduced due to technological advances and demands for higher coverage.
Keywords: G22; 650; Insurance market; Motor hull insurance; Liability insurance; GAP insurance; Pay-As-You-Drive Insurance